Molecular Characterization of Rotifers and Their Potential Use in the Biological Control of Biomphalaria - Lin, Datao; Xiang, Suoyu; Sanogo, Benjamin; Liang, Yousheng; Sun, Xi; Wu, Zhongdao (Frontiers in Cellular and Infection Microbiology, 2021)
Background Schistosomiasis is one of the most important tropical parasitic diseases worldwide. Biomphalaria straminea, the intermediate host of Schistosoma mansoni, has invaded and spread to Southern China since 1974 and may pose enormous threats to public health. Controlling intermediate host snails is an effective strategy in schistosomiasis intervention. However, the only effective chemical molluscicide, niclosamide, currently recommended by World Health Organization may cause environmental pollution, the loss of biodiversity, and high costs. Thus, to counter intermediate hosts, a sustainable and environmentally friendly tool is urgently needed. Here, we conducted field investigations to collect and identify a potential snail competitor rotifer and evaluated its molluscicide effect. Results In this study, we collected two samples of rotifers from Shenzhen. We found both red and black phenotypic B. straminea snails at the sampling sites. We identified the rotifer population as a species of the genus Philodina according to the amplification and phylogenetic analysis results of the coxⅠ gene. We found that rotifer exposure did not significantly affect the hatching rate of Biomphalaria straminea eggs but promoted the killing of juvenile snails. Meanwhile, rotifer exposure did not significantly alter the fecundity of Biomphalaria straminea quantified by the number of eggs per egg mass, the number of egg masses per snail, and the number of eggs per snail, but the snails exposed to rotifers showed lower fecundity performance than the control snails. Importantly, rotifer exposure could significantly affect the development of juvenile Biomphalaria straminea, showing a smaller shell diameter of exposed snails than that of control snails. In addition, rotifer exposure affected the life span of B. straminea snails, showing a 16.61% decline in the average life span. After rotifer exposure, the S. mansoni-infected Biomphalaria straminea snails died significantly faster than those without rotifer exposure. Similar findings were observed in Schistosoma mansoni-infected Biomphalaria glabrata snails. These results implied that rotifer exposure significantly promoted the mortality of Schistosoma mansoni-infected Biomphalaria straminea and Biomphalaria glabrata. Conclusions Our study demonstrated the potential molluscicide effect of rotifers on intermediate hosts under laboratory conditions. Our findings may provide new insights into the development of biocontrol strategies for snail-borne disease transmission.